MENGEMBANGKAN KEMAMPUAN MOTORIK ANAK USIA DINI MELALUI RANGSANGAN AUDIO DI TK IBUNDA KUBANG - Novalia, Frizia Nuary; Yuliasma, Yuliasma (SENDRATASIK UNP, 2019)
Abstract The purpose of this study was to develop motoric skills of early childhood by using audio stimulation at Ibunda Kubang Kindergarten in Kerinci Regency. The type of this research was PTK (Classroom Action Research). The procedures of this study were divided into 2 cycles, namely cycle I and cycle II. The instrument of this research used observation and documentation sheets. Then, the data collection techniques were carried out by observation, gross motor ability tests and documentation. Next, the results showed that the gross motor ability of children in the learning process seemed developed by using Audio Stimulation in the childer of group B  at Ibunda Kubang Kindergarten, Kerinci Regency. Audio Stimulation can develop children's gross motor ability as an increase in each cycle. In cycle I, there was an increase in children's gross motor ability for each meeting, but the minimum completeness criteria (KKM) had not reached yet. They were  namely the first aspect 21.4%, the second aspect 28.6% and the last aspect 21.4%. Whereas in the second cycle there was an increase and the results had fulfilled and for KKM it was established. they were 21.4% to 85.7% (at fisrt aspect), 28.6% to 85.7%  (at the second aspects) and the last aspect 21.4% to 78.6 %. Audio Stimulation can develop children's gross motor ability at Ibunda Kubang Kindergarten. So this Audio Stimulation is good to be used for improving the gross motor ability of children. Keywords: developing, motoric ability of early childhood, audio stimulation